Law No. 3 of the year 2013 concerning Exempting the Establishments And the Insured From the Additional Amounts due thereon to the National Organization for Social Insurance = قانون رقم 3 لسنة 2013 بشأن إعفاء المنشآت والمؤمن عليهم من المبالغ الإضافية المستحقة عليهم للهيئة القومية للتأمين الاجتماعى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.